ChemInform Abstract: Photocatalysis by 3, 6‐Disubstituted‐s‐tetrazine: Visible‐Light Driven Metal‐Free Green Synthesis of 2‐Substituted Benzimidazole and Benzothiazole. Issue 15 (15th April 2014) - Samanta, Suvendu; Das, Sudipto; Biswas, Papu
Abstract 3, 6‐Di(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine exhibits effective visible light absorption and reversible one‐electron reduction behavior.